2003
DOI: 10.1105/tpc.010678
|View full text |Cite
|
Sign up to set email alerts
|

SPL8, an SBP-Box Gene That Affects Pollen Sac Development in Arabidopsis

Abstract: SQUAMOSA PROMOTER BINDING PROTEIN-box genes (SBP-box genes) encode plant-specific proteins that share a highly conserved DNA binding domain, the SBP domain. Although likely to represent transcription factors, little is known about their role in development. In Arabidopsis, SBP-box genes constitute a structurally heterogeneous family of 16 members known as SPL genes. For one of these genes, SPL8 , we isolated three independent transposon-tagged mutants, all of which exhibited a strong reduction in fertility. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
214
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(225 citation statements)
references
References 40 publications
3
214
0
1
Order By: Relevance
“…In addition, the study of mutants exhibiting stage-specific defects in microsporogenesis and pollen release has further advanced our understanding of the process (Preuss et al, 1993;Sanders et al, 1999;Park and Twell, 2001; Azumi et al, 2002; Steiner-Lange et al, 2003; Unte et al, 2003). Although little is known about how GA controls stamen filament elongation, anther development or microsporogenesis, there have been previous suggestions that GA-signalling components may modulate these processes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study of mutants exhibiting stage-specific defects in microsporogenesis and pollen release has further advanced our understanding of the process (Preuss et al, 1993;Sanders et al, 1999;Park and Twell, 2001; Azumi et al, 2002; Steiner-Lange et al, 2003; Unte et al, 2003). Although little is known about how GA controls stamen filament elongation, anther development or microsporogenesis, there have been previous suggestions that GA-signalling components may modulate these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Most likely being a transcription factor (Birkenbihl et al 2005), SPL8 has previously been shown to be required for proper micro-and megasporogenesis as deduced from its semi-sterile mutant phenotype (Unte et al 2003). In this study, we generated SPL8 gain-of-function transgenic lines.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few functions for SBP domain proteins have been reported, perhaps due to genetic redundancy of closely related family members. In all cases, SBP domain proteins have been implicated in various aspects of plant growth and development, including metal sensing in algae and directing development of leaves, embryos, and floral organs in higher plants (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Some of these SBP do-main proteins may also be posttranscriptionally regulated by noncoding microRNAs to control their spatial and temporal expression (23)(24)(25).…”
mentioning
confidence: 99%